Chlorophyta, Xanthophyceae and Cyanobacteria in Wright Valley, Antarctica. Issue 5 (22nd April 2015) - Novis, Phil M.; Aislabie, Jackie; Turner, Susan; McLeod, Malcolm
Abstract: Wright Valley, Victoria Land contains numerous aquatic habitats suitable for the growth of algae in summer. Excepting diatoms and lichen phycobionts, algal diversity and distribution in the valley was documented. Using cultures and environmental cloning eight cyanobacterial and 14 eukaryotic species were revealed. The cyanobacterium Microcoleus vaginatus and the chlorophycean Chlorococcum sp. 1 were the most common, both occurring in more than one habitat (ponds, soils or streams). Ponds harboured the most diverse communities. Habitat specialization was rare. Chlamydomonads were not found outside ponds, but species capable of zoospore production were able to colonize ponds and soils. Nostocalean cyanobacteria were not detected. Results suggest dispersal within and between valleys, with little evidence of Antarctic endemism. All but one cyanobacterium with similar internally transcribed spacer (ITS) length to clones from Miers Valley proved to be different species when 16S rRNA gene sequences were also considered; thus, ITS length is unreliable for assessing identity and biogeography of these cyanobacteria. Comparison with a 454 16S rRNA gene soil dataset from Wright Valley indicated the occurrence of only one of the cyanobacterial species, the distribution of which may be limited by salinity.